Social Criticism Over Art, Culture and Space in Aldous Huxley’s Travelogues - Dangaura, Mohan (JODEM: Journal of Language and Literature, 2025)
This essay examines how Aldous Huxley’s travelogues depict art, culture, and space from a realistic and socially critical standpoint. In the following short travelogues: “Between Peshawar and Lahore,” “Guatemala City,” “Agra,” “Japan,” “Benares,” and “Copan,” he critiques the behavior of people, art, architecture, and other locations by making observations about their actuality, popularity, genuine values, and frivolity. He attacks the Indian subcontinent’s populace for seeing themselves as divine beings and for frequently deceiving and intimidating the weak and impoverished. He critically observes and analyzes well-known historic and religious sites while traversing India. Depending on their critical consciousness and scientific conscience, he finds common people of India either engaging in more restrictive rituals or spiritually following the persons like Baba, Jogi, or Swami. He also comments on Japanese folk performances for lacking the creativity and engagement in their performances. Hence, he considers internal politics, poverty, and illiteracy as the main factors contributing to the degradation of historic world heritage sites, artwork, and the history of major civilizations in Latin American nations. The study applies William Raymond and Willis Truitt’s concepts of realism to theoretically support the arguments.